Demokrasi, Negara Indonesia - Haryati S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2007)
To get legal certainty and legal right of the right in land, the land needs to be registered in the Departement of land affair for holding avalid evidence. A valid evidence means Cerificate of Ownership can be abtained by registering the right in land. The function of the Certificate of Ownership for ensure the owner in land other parties.